2020
DOI: 10.1097/md.0000000000019530
|View full text |Cite
|
Sign up to set email alerts
|

Association between CD24 Ala/Val polymorphism and multiple sclerosis risk

Abstract: Background: The aim of this study was to explore the association between CD24 Ala/Val polymorphism and susceptibility of multiple sclerosis (MS). Methods: A comprehensive literature search for relevant studies was performed on google scholar, PubMed, Web of science, Embase, the Chinese National Knowledge Infrastructure and the Chinese Biology Medicine. This meta-analysis was conducted using the STATA 11.0 software and the pooled odds ratio with 95% confidence interval w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…GO and REACTOME pathway enrichment analyses were used to explore the molecular mechanisms of the genes involved in the occurrence and development of MS. It is well known that the pathways include immune system [55], TCR signaling [56], cytokine signaling in immune system [57], degradation of the extracellular matrix [58], extracellular matrix organization [58], metabolism of lipids [59] and metabolism [60] plays an important role only in MS. CCL18 [61], FCRL3 [62], EOMES (eomesodermin) [63], CCR2 [64], IL2RB [65], CCL4 [66], FASLG (Fas ligand) [67], CD24 [68], IKZF3 [69], CD2 [70], CD28 [71], IL7R [72], HLA-DRB5 [73], ICOS (inducible T cell costimulator) [74], CCL5 [75], CTLA4 [76], IRF4 [77], C6 [78], NCR1 [79], CHIT1 [80], CD52 [81], CD163 [82], HGF (hepatocyte growth factor) [83], DIO3 [84], SIGLEC1 [85], TTR (transthyretin) [86], IL9 [87], VEGFA (vascular endothelial growth factor A) [88], CR2 [89], ANGPTL4 [90], CHI3L1 [91], MAG (myelin associated glycoprotein) [92], CNP (2’,3’-cyclic nucleotide 3’ phosphodiesterase) [93], CMTM5 [94], SEMA4D [95], NGFR (nerve growth factor receptor) [96], TF (transferrin) [97], MYRF (myelin regulatory factor) [98], MOG (myelin oligodendrocyte glycoprotein) [99], ADAMTS4 [100], BMP2 [101], HTRA1 [102], PNPLA3 [103], DYSF (dysferlin) [104], NINJ2 [105], LRP2 [106], ADAMTS14 [107] and DHCR7 [108] might play an important role in regulating the occurrence and development of MS. The expression of CCL18 [109], SLAMF7 [110], GPR174 [111], CCR4 [112], POU4F2 [113].…”
Section: Discussionmentioning
confidence: 99%
“…GO and REACTOME pathway enrichment analyses were used to explore the molecular mechanisms of the genes involved in the occurrence and development of MS. It is well known that the pathways include immune system [55], TCR signaling [56], cytokine signaling in immune system [57], degradation of the extracellular matrix [58], extracellular matrix organization [58], metabolism of lipids [59] and metabolism [60] plays an important role only in MS. CCL18 [61], FCRL3 [62], EOMES (eomesodermin) [63], CCR2 [64], IL2RB [65], CCL4 [66], FASLG (Fas ligand) [67], CD24 [68], IKZF3 [69], CD2 [70], CD28 [71], IL7R [72], HLA-DRB5 [73], ICOS (inducible T cell costimulator) [74], CCL5 [75], CTLA4 [76], IRF4 [77], C6 [78], NCR1 [79], CHIT1 [80], CD52 [81], CD163 [82], HGF (hepatocyte growth factor) [83], DIO3 [84], SIGLEC1 [85], TTR (transthyretin) [86], IL9 [87], VEGFA (vascular endothelial growth factor A) [88], CR2 [89], ANGPTL4 [90], CHI3L1 [91], MAG (myelin associated glycoprotein) [92], CNP (2’,3’-cyclic nucleotide 3’ phosphodiesterase) [93], CMTM5 [94], SEMA4D [95], NGFR (nerve growth factor receptor) [96], TF (transferrin) [97], MYRF (myelin regulatory factor) [98], MOG (myelin oligodendrocyte glycoprotein) [99], ADAMTS4 [100], BMP2 [101], HTRA1 [102], PNPLA3 [103], DYSF (dysferlin) [104], NINJ2 [105], LRP2 [106], ADAMTS14 [107] and DHCR7 [108] might play an important role in regulating the occurrence and development of MS. The expression of CCL18 [109], SLAMF7 [110], GPR174 [111], CCR4 [112], POU4F2 [113].…”
Section: Discussionmentioning
confidence: 99%
“…CD24 is expressed on a broad range of cells in the central nervous systems (CNS) and is related to the development of experimental autoimmune encephalomyelitis in mice. There are increasing studies focus on the association of a CD24 Ala/Val coding polymorphism with the susceptibility and progression of multiple sclerosis (12). It is reported that CD24 deficient mice could be more susceptible to danger associated molecular patterns but not pathogen-associated molecular patterns.…”
Section: Cd24 In Autoimmune Diseases and Other Disordersmentioning
confidence: 99%